The Strategy Focuses of Recreation and Tourism Activities of Ichnia National Nature Park (Ukraine) Design Employing Canvas Business-model and SWOT-analysis - Kiptenko Viktoriia (EDP Sciences, 2021)
National parks across the world contribute to the preservation of biodiversity, playing simultaneously an outstanding role in sustainable activities, recreation and tourism in particular. Experience with COVID-19 shows that resilience is fundamental to the sustainability of protected area visitation, which was affected in different ways by pandemics. The last decade challenges for the national nature parks of Ukraine, positive impetuses of several successful projects, enhancement of the community role in the environmental issues caused the search for a framing of the strategy of recreation and tourism activity of the national nature park located in Ichnia, Chernihiv oblast, Ukraine. By employing the Canvas business model and SWOT analysis the client-oriented shift in the above park strategy focuses ground prospects for facts-based decision-making and planning. The focuses advised include restructuring of the organizational patterns of the entity; modernisation of information and communication activities; profiling of demand and diversification of values for travellers of different motivation; networking with stakeholders.